Association between the incidence of early childhood caries and attending childcare among toddlers in a rural area of Japan: a prospective cohort study. (17th February 2021) - Yokoi, Aya; Takeuchi, Noriko; Ekuni, Daisuke; Morita, Manabu
Abstract: Objective: The purpose of this study was to investigate the association between the incidence of early childhood caries (ECC) and factors of the daytime childcare environment among toddlers in a rural area of Japan. Material and methods: This was a prospective cohort study. Data collected from 2011 to 2015 were obtained for initially caries-free, 18-month-old toddlers ( N  = 640). Dentists recorded the numbers of decayed, missing and filled teeth (caries incidence) of toddlers at baseline (age 18 months) and follow-up (age 3 years). In addition, a questionnaire survey was conducted on guardians at baseline to record data on lifestyle. Results: In total, 159 (24.8%) toddlers had newly identified ECC at follow-up. Logistic regression analyses indicated that the incidence of ECC was significantly associated with receiving daytime care at a nursery school (odds ratio [OR], 1.55; 95% confidence interval [CI], 1.05–2.30; p  = .029), prolonged breastfeeding (OR, 1.71; 95%CI, 1.15–2.55; p  = .008), and snacking ≥3 times a day (OR, 2.39; 95%CI, 1.53–3.74; p  < .001). Conclusion: These findings suggest that receiving daytime care at a nursery school, prolonged breastfeeding, and frequent snacking are associated with an increased risk of ECC among Japanese toddlers in rural areas.